STUDI SIFAT MEKANIK PROTEIN L DENGAN PENDEKATAN SIMULASI STEERED MOLECULAR DYNAMICS - Aditama, Reza
Protein L is an immunoglobulin protein, which has been known to have a rigid substructure, when it was stretched by atomic force microscope (AFM) in the previous study. The AFM experiment, however, was not able to provide information about the precise location of the rigid substructure in protein L and also the factors responsible for its mechanical property due to the limitation in the capability of the instrument. This problem was handled in the current study by simulating the stretching experiment with steered molecular dynamics (SMD) method. In this work, protein L was stretched by fixing one of the terminal atom and pulling from the other one with a constant velocity (0.5 Å/ps and 0.1 Å/ps) and with a constant force (600 and 750 pN). Similar to the experimental result, our simulation was also able to detect the presence of the rigid substructure. Further analysis to the simulation trajectory revealed that the rigid substructure of the protein L was the parallel b-sheet located in the C-terminal region, whose structure was mainly stabilized by the cluster of hydrogen bonds.